Deterioration of Li-doped phenanthroline-based charge generation layer for tandem organic light-emitting diodes - Ki Ju Kim; Sunwoo Kang; Taekyung Kim (Journal of Information Display)
Understanding the deterioration of the charge generation layer (CGL) is an uprising issue for efficient and stable tandem organic light-emitting diodes. Here, we comprehensively investigated the change in the electrical characteristics of Li-doped CGLs according to different stress conditions and compared the stability of Li diffusion in two phenanthroline-based electron transport materials. Through current density–voltage and capacitance-frequency measurements, it was revealed that electrical stress and thermal stress affect CGL’s electrical properties differently. Moreover, the exponential trap distribution model analysis informed that the Li diffusion is expedited toward narrowing depletion width in the CGL. Diffusion of Li and thermal effect to the diffusion was experimentally observed by X-ray photoelectron spectroscopy (XPS) depth profiling. We also evaluated variations in the operating voltage of tandem devices that differed only in nCGL. Overall, Li diffusion occurs more favorably in sparse Bphen film with weak binding energy rather than closely packed BPPB film with strong binding energy, which highlights that atomic geometry and morphological characteristics are crucial for the stability of tandem devices.